2017
DOI: 10.1002/slct.201600998
|View full text |Cite
|
Sign up to set email alerts
|

Gel–based Controlled Synthesis of Silver Nanoparticles and Their Applications in Catalysis, Sensing and Environmental Remediation

Abstract: We report herein a novel gel-based method of generating silver nanoparticles (AgNPs) for various applications. An unorthodox pyridyl-pyrazole basedchelatinglow molecular mass gelator was used for controlled synthesis of multifunctional AgNPs. The resultant fiber networks of gel itself act as template for AgNPs formation when a threshold concentration of Ag salts is exceeded. It is noteworthy here that existence of such threshold condition for AgNP formation is strategically important but under explored. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…They have potential for the adsorption of pollutants because small molecules or metal ions can rapidly diffuse within them easily. The interaction between the gel network and the contaminants causes the contaminants to be effectively fixed inside the gel, , and catalytic centers are readily loaded in the gel matrix for efficient catalysis. For example, Zhang et al reported a metal–organic gel featuring a catalytic binding pocket to benefit synergistic catalysis for acryl-transfer reactions . Hawkins et al reported that a chiral gel of benzaldehyde and glutamine amide can catalyze the prebiotically relevant aldol dimerization of glycolaldehyde .…”
Section: Introductionmentioning
confidence: 99%
“…They have potential for the adsorption of pollutants because small molecules or metal ions can rapidly diffuse within them easily. The interaction between the gel network and the contaminants causes the contaminants to be effectively fixed inside the gel, , and catalytic centers are readily loaded in the gel matrix for efficient catalysis. For example, Zhang et al reported a metal–organic gel featuring a catalytic binding pocket to benefit synergistic catalysis for acryl-transfer reactions . Hawkins et al reported that a chiral gel of benzaldehyde and glutamine amide can catalyze the prebiotically relevant aldol dimerization of glycolaldehyde .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have found applications in multiple fields over the years, ranging from fuel cell catalysts, magnetic resonance imaging contrast agents in medicine, lubrication, environmental remediation, , to catalysis . Given the context of the COVID-19 pandemic, the creation of contact surfaces and fabrics that can kill virus particles upon microbe exposure is an urgent scientific challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy here that arresting a heavy metal-coordinated network in the gel state especially using low-molecular-weight gelators itself is a formidable task. Needless to say, successful execution of such a task primarily depends on the ligand design. Any judicious design of a heavy metal gelator offers a three-pronged challenge: first, to fit with functional groups containing multiple coordinating sites similar to a typical toxic metal capturing agent; second, the spatial arrangement of functionalities should ensure forming a highly cross-linked, intertwined, three-dimensional network; and finally, to modify the chassis of the ligand particularly the noncoordinating part with functionalities capable of immobilizing a large amount of solvent molecules within the framework, thus fulfilling the most important prerequisite of gelation . In a nutshell, the two-in-one ligand should be a heavy metal capturing agent that also capable of gelation …”
Section: Introductionmentioning
confidence: 99%